Presentasi Diri Waria melalui Media Sosial Instagram di Kota Palembang - Qorry Faula (Jurnal Empirika, 2021)
This research is titled "Self-Presentation of Shemale Through on Social Media Instagram in Palembang City". Shemale are considered deviant behaviour so that people cannot accept their existence, but the self-presentation they present on Instagram makes the person who sees become entertained. This research aimed to understand the self-presentation of shemale through social media Instagram in Palembang City. The qualitative method used determines informants by purposive means of obtaining data and information from individuals who know the problems raised. The findings were obtained from observations, in-depth interviews, and subsequent data analysis using Dramaturgy Theory from Erving Goffman. This research showed that self-presentation displayed shemale through social media Instagram as an entertainer. Shemale will manage the impression to present the appearance of an entertainer in photos and videos uploaded to Instagram that become the stage of the show and keep their daily activities secret that can interfere with the delivery of impressions to the audience.